Avaliação da coagulação e cicatrização de alvéolos dentários de ratos submetidos a exodontia em uso de diferentes doses de varfarina - Ferreira, Isaquiel Chaves (2024)
The flow of patients in dental offices using warfarin is frequent. Therefore, experimental animal models are necessary to understand the changes in coagulation and alveolar healing. In order to evaluate the effect of warfarin therapy, at different doses, on coagulation and bone healing after tooth extraction in Wistar rats, we distributed 96 male Wistar rats (200 - 250 g) into twelve experimental groups (n = 8 in each group). First, on day D0, blood was collected from all animals for complete blood count, prothrombin time (PT) and international normalized ratio (INR). On day D1, daily administration of saline solution (groups 1, 5, and 9) or warfarin at concentrations of 0.05 mg/kg (groups 2, 6, and 10), 0.10 mg/kg (groups 3, 7, and 11), and 0.20 mg/kg (groups 4, 8, and 12) by gavage was initiated. On day D6, all animals had their first lower left molar removed, followed by blood collection. Euthanasia occurred one hour (1 h) after tooth extraction (D6) for animals in groups 1-4, one day after tooth extraction (D7) for animals in groups 5-8, and thirty days after tooth extraction (D36) for animals in groups 9-12. The mandibles were collected for radiographic, histomorphometric, and histochemical analyses. The data were subjected to one-way ANOVA statistical analysis followed by the Bonferroni post-test (p<0.05, GraphPad Prism v20.0 statistical software). The doses of 0.10 (p<0.05) and 0.20 mg/kg (p<0.05) increased the PT and INR on the 6th day in relation to D0. In the radiographic analysis, there was a reduction in the radiolucent area 30 days after tooth extraction in animals that received the dose of 0.10 (p<0.05) and 0.20 mg/kg (p<0.05), in relation to the control group. When analyzing fibrin deposition, the dose of 0.20 mg/kg (p<0.05) reduced the amount of fibrin in the 1st hour and the doses of 0.05; 0.10 and 0.20 mg/kg (p<0.05) reduced fibrin after 24 hours, when compared with the control groups. In the histomorphometric analysis, the dose of 0.05 mg/kg (p<0.05) reduced the amount of polymorphonuclear cells in the alveolus on the 30th day, in relation to the control, and the dose of 0.20 mg/kg reduced osteoclasts (p<0.05) and total collagen (p<0.05) after 30 days of extraction. Furthermore, the doses of 0.05; 0.10 and 0.20 mg/kg (p<0.05) reduced type III collagen on the 30th day after extraction, in relation to the control. Therefore, the administration of warfarin at doses of 0.10 and 0.20 mg/kg was able to establish a new experimental model of coagulation deficit in rats subjected to tooth extraction and treated with warfarin. However, the dose of 0.20 mg/kg alters the alveolar healing of the rats due to the reduction of osteoclasts, modifying bone remodeling and collagen deposition.